In the realm of gods and kings : arts of India - Desai, Vishakha N. (2004)
[Dt.:] Die Ausstellung zeigt Bilder und Plastiken aus der Sammlung von Cynthia und Leon Polsky. Insgesamt sind auf den Internetseiten 13 Exponate zu sehen. Die Ausstellung wurde von der Asia Society und dem Metropolitan Museum of Art ausgerichtet. Zu lesen ist zudem ein Artikel von Julie Rauer zur Polsky Sammlung und Auszüge aus dem Vorwort zu dieser Ausstellung von Vishakha N. Desai. - [Engl.:] This online exhibition shows parts of the Polsky Collections (Cynthia and Leon Polsky). Their collection is less about things themselves as about what these things say about the special qualities of India; its capacity to contemplate big philosophical ideas in seemingly ordinary places, its tenacity to hold onto ideas and images from thousand years back, and always, its ability to create coherence out of chaos. There are also available a article written by Julie Rauer about this collection.